1 Week 1 Story Bulletin of School of Information Science UiTM Sarawak: Oktober 2023 - Februari 2024 - Halamy, Suhaida; Ibrahim, Imilia; Ismailly, Norlida; Salji, Mohd Rafiz; Mohd Jawi, Abdul Ismail; Jamil, Nurul Huda Izzati; Abdul Samad, Sabariah; Sulaiman, Sharin; Zaini, Favilla; Jack, Suriani; Haji Bibi, Zainon (Perpustakaan Tun Abdul Razak UiTM Sarawak, 2024)
It gives me great pleasure to be part of the Information Science community as we commemorate the 20th anniversary of the School of Information Science in UiTM Sarawak branch. From a humble beginning of 12 students and 2 lecturers in 2003, the program has thrived and continued to push boundaries. By the onset of 2024, there are 376 students and 14 lecturers. The school continued to excel in academics and ignite innovation, research, and community engagement. Indeed, this is a journey of inspiration. This remarkable journey would not have been possible without the support of our lecturers. Hence, I would like to take this opportunity to express my deepest gratitude to all our lecturers for their unwavering dedication, commitment, and support in transforming our students. You are truly the beacon of our school and students! Therefore, as we celebrate this 20-year milestone, let us all continue to strive together, shaping a brighter tomorrow for generations to come. The other pillar of the School of Information Science is none other than our enthusiastic students. I admire their noble aspiration and the strong desire to make a positive impact on our society. As mentors, it is our privilege to empower them in pursuing their aspirations. I hope that they will continue to enrich themselves with educational experience, never stop learning, continue giving back to our society and become leaders in their own right. Lastly, I wish to thank each and every one for the hard work in making this bulletin a reality. My appreciation goes out to all the contributors in this volume. Your insights and perspectives have enriched this bulletin.